Challenges of public-school elementary mathematics teaching in the new normal - Ramiro Z. dela Cruz; Gloria D. Hernandez (Indonesian Journal of Social Sciences, 2023)
At the onset of the Covid-19 pandemic, educational institutions worldwide needed to continue with their educational mandates for their learners, albeit not in the usual face-to-face modes. The Higher Education Institutions (HEIs) in the Philippines as well had to replace the on-campus teaching-learning modes with several variants of remote teaching. However, the various remote means are something quite new to both educators and learners, especially in mathematics, wherein various onboard instructions and on-desk hands-on exercises had been the norm. This study used of quantitative approach through online surveys to identify the educators’ challenges with remote teaching implementations in public schools in the Philippines. The findings reveal challenges related to the actual delivery of mathematics instruction, distractions from non-teaching tasks, curricular adjustments, alignment of materials, and orientation of parents or guardians and teachers. The pandemic may not be the last to impact the education system. Overall, the study shows an increased level of challenges for mathematics teaching. Thus, there is an urgent need to readjust policies and procedures affecting environmental learning conditions such as distractions, family-work-life balance, communication technology, rationalization of non-academic duties, increased participation, and support of parents and guardians.